2022
DOI: 10.3390/pharmaceutics14071418
|View full text |Cite
|
Sign up to set email alerts
|

“Endothelial Antibody Factory” at the Blood Brain Barrier: Novel Approach to Therapy of Neurodegenerative Diseases

Abstract: The failures of anti-β-amyloid immunotherapies suggested that the very low fraction of injected antibodies reaching the brain parenchyma due to the filtering effect of the BBB may be a reason for the lack of therapeutic effect. However, there is no treatment, as yet, for the amyotrophic lateral sclerosis (ALS) despite substantial evidence existing of the involvement of TDP-43 protein in the evolution of ALS. To circumvent this filtering effect, we have developed a novel approach to facilitate the penetration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, to this day, clinical trials based on EPCs transplantation have not provided successful outcomes [ 6 ] or are still ongoing [ 7 ]. Our research showed recently that EPCs injected into mice could migrate into the brain and play as successful providers of the gene construct to destroy the proteins involved in Alzheimer’s disease (AD) [ 8 ]. EPC dysregulation has been observed in patients suffering from AD showing contradictory outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, to this day, clinical trials based on EPCs transplantation have not provided successful outcomes [ 6 ] or are still ongoing [ 7 ]. Our research showed recently that EPCs injected into mice could migrate into the brain and play as successful providers of the gene construct to destroy the proteins involved in Alzheimer’s disease (AD) [ 8 ]. EPC dysregulation has been observed in patients suffering from AD showing contradictory outcomes.…”
Section: Introductionmentioning
confidence: 99%